Elaboración del estudio de prefactibilidad para el montaje del centro de conectividad y cultura Cibercity en Bogotá (2014)
This document presents the results of the final report of the degree work entitled "Pre-feasibility study for the assembly of the CiberCity connectivity and culture center in Bogotá". The product of the project is the CiberCity connectivity and culture center whose main purpose is to expand coverage of access to information and contribute to the promotion of the culture of the Bogota population, through a space of connectivity, entertainment and learning, making use of state-of-the-art information technology tools.